Management of Thoracic Disc Herniation Using the Mini-Open Retropleural Approach: Technique Illustration and Clinical Outcomes of 33 Patients From a Single Academic Center. (18th November 2021) - Noureldine, Mohammad Hassan A; Pressman, Elliot; Krafft, Paul R; Molcanyi, Marek; Tran, Nam D; Greenberg, Mark S; Alikhani, Puya
Graphical Abstract: